1973
DOI: 10.3758/bf03199074
|View full text |Cite
|
Sign up to set email alerts
|

The effect of redundant contextual stimuli on autoshaping the pigeon’s keypeck

Abstract: Three experiment, investigated the effect of contextual and trial stimulus lighting conditions on keypeck autoshaping in pigeons. White illumination of a response key before food presentation readily produced keypecking in a brightly lit chamber but failed to do so in a chamber without house illumination (Experiments I and III). Keypecking in 3 darkened cubicle progressively increased and the facilitatory effect of a houselight decreased as the keylight stimulus W3< varied from 3 color change (Experiment II) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0
2

Year Published

1975
1975
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 21 publications
6
48
0
2
Order By: Relevance
“…A variety of different trends in the temporal distribution of key pecks across delay autoshaping trials has been observed (Baldock, 1974;Gardner, 1969;Moore, 1971;Ricci, 1973;Wasserman, 1973). Some pigeons in the 8-sec delay group of Experiment I exhibited each of these trends, and no particular trend represented the group.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A variety of different trends in the temporal distribution of key pecks across delay autoshaping trials has been observed (Baldock, 1974;Gardner, 1969;Moore, 1971;Ricci, 1973;Wasserman, 1973). Some pigeons in the 8-sec delay group of Experiment I exhibited each of these trends, and no particular trend represented the group.…”
Section: Resultsmentioning
confidence: 96%
“…Foree and LoLordo (1973) showed that, given a history of treadle pressing for food in the presence of a compound houselight-tone stimulus, pigeons' responding was controlled by the houselight, but not by the tone, when it was presented alone, suggesting that the salience of tones may be very low in food situations. Wasserman (1973) exposed pigeons to keylight changes preceding food under two conditions: houselight always or never illuminated. The birds with the houselight pecked the key, and those without failed to peck the key.…”
Section: Experiments IIImentioning
confidence: 99%
“…That is, keypecking and prekeypecking behaviors are not independent but, rather, contingencies applied to one behavior also affect the other. The nonindependence of keypecking and offkeypecking is also supported by the frequent appearance of offkeypecking during punishment procedures (Bachrach, 1966;Dunham, Mariner, & Adams, 1969), response-independent procedures (Staddon & Simmelhag, 1971), and other autoshaping procedures (Brown & Jenkins, 1968;Wasserman, 1973a). The present study supports these findings and suggests that the failure of keypeck omission training to eliminate keypecking during automaintenance schedules results because prekeypecks similar in location and topography to keypecks are ad ven titiously reinforced during automaintenance schedules.…”
Section: Discussionmentioning
confidence: 98%
“…The left and right keys could be activated when contact exceeded IS g (.15 N), and they could be trans illuminated white, green, or red when 28-V de was applied to miniature incandescent bulbs (ESB 24). Directly above the center key was the houselight, which provided general chamber illumination during the experimental sessions (see Wasserman, 1973) when 6.3-V ac was applied to an encased bulb (GE 44). Directly below the center key was the hopper opening through which grain reinforcers were made available when the hopper was elevated and illuminated.…”
Section: Apparatusmentioning
confidence: 99%